2020
DOI: 10.1080/13825585.2020.1727834
|View full text |Cite
|
Sign up to set email alerts
|

Risk- and protective factors for memory plasticity in aging

Abstract: Risk and protective factors for cognitive function in aging may affect how much individuals benefit from their environment or life experiences by preserving or improving cognitive abilities. We investigated the relations between such factors and outcome from episodic-memory training in 136 healthy young and older adults. Tested risk factors included carrying the ɛ4 variant of the apolipoprotein E allele (APOE), age, body mass index, blood pressure, and cholesterol. Protective factors included higher levels of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 76 publications
(95 reference statements)
0
8
0
Order By: Relevance
“…The XGBoost model is based on a decision‐tree ensemble algorithm that includes advanced regularization to reduce overfitting (Chen & Guestrin, 2016), and uses a gradient boosting framework where the final model is based on a collection of individual models (https://github.com/dmlc/xgboost). To optimize hyperparameters, a randomized search was performed with 10 folds for each model, with scanned parameter ranges set to maximum depth : (Bennett & Madden, 2014; Bråthen et al, 2020; Grady, 2012), number of estimators : [60, 220, 40], and learning rate : [0.1, 0.01, 0.05]. The optimized parameters were maximum depth = 2, number of estimators = 180, and learning rate = 0.1 for the brain age model, and maximum depth = 2, number of estimators = 140, and learning rate = 0.05 for the cognitive age model.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The XGBoost model is based on a decision‐tree ensemble algorithm that includes advanced regularization to reduce overfitting (Chen & Guestrin, 2016), and uses a gradient boosting framework where the final model is based on a collection of individual models (https://github.com/dmlc/xgboost). To optimize hyperparameters, a randomized search was performed with 10 folds for each model, with scanned parameter ranges set to maximum depth : (Bennett & Madden, 2014; Bråthen et al, 2020; Grady, 2012), number of estimators : [60, 220, 40], and learning rate : [0.1, 0.01, 0.05]. The optimized parameters were maximum depth = 2, number of estimators = 180, and learning rate = 0.1 for the brain age model, and maximum depth = 2, number of estimators = 140, and learning rate = 0.05 for the cognitive age model.…”
Section: Methodsmentioning
confidence: 99%
“…Interindividual differences within older adult populations have led to a large number of studies focusing on risk and protective factors for cognitive decline in aging (Anatürk, Demnitz, Ebmeier, & Sexton, 2018; Bråthen, Lange, Fjell, & Walhovd, 2020; Nyberg, Fjell, & Walhovd, 2019; Sabia et al, 2019; Zsoldos et al, 2018), as well as factors that characterize successful aging or “SuperAgers” (Gefen et al, 2014; Harrison, Weintraub, Mesulam, & Rogalski, 2012; Rogalski et al, 2013; Yu et al, 2019). The maintenance of a “younger” brain, that is, the relative lack of aging‐related changes including pathology, has been suggested as a main mechanism to preserve cognitive function into older age (Nyberg et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Finally, being female appeared to be another protective factor of cognitive decline, especially with controlling GSH level change from baseline to endpoint ( p = 0.040 in Table 4 ). Similarly, a recent study found that being female was a marginal protective factor of cognitive function in aging after memory training [ 35 ]. However, in another study, women with MCI were more likely to decline in cognitive function than men [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…A decline in episodic memory performance has been widely characterized as a hallmark symptom of a number of age-related neurological conditions, particularly Alzheimer’s disease (AD; Tromp et al ., 2015; El Haj et al ., 2016), but it has also been associated with neurocognitive aging in healthy adults (Cansino, 2009; Salthouse, 2010; Grady, 2012). Despite the age-related episodic memory decline, there is considerable interindividual variability in memory performance in older adults, presumably due to protective factors for age-related neurocognitive declines (Cansino, 2009), such as physical activity (Lee et al ., 2010; Bherer et al ., 2013), education (Hendrie et al ., 2006), and intelligence capacities (Bråthen et al ., 2021). At personality trait level, the Big Five trait Openness to Experience (hereafter: Openness) has been associated with episodic memory performance (Gregory et al ., 2010; Terry et al ., 2013; Curtis et al ., 2015; Luchetti et al ., 2016; Sutin et al ., 2019), with older adults scoring high in this trait showing better memory performance.…”
Section: Introductionmentioning
confidence: 99%